2021
DOI: 10.31004/edukatif.v4i1.1940
|View full text |Cite
|
Sign up to set email alerts
|

Dampak Kebijakan Merdeka Belajar Kampus Merdeka (MBKM) pada Perguruan Tinggi Swasta di Indonesia

Abstract: Merdeka Belajar Kampus Merdeka (MBKM) adalah program pembelajaran pendidikan tinggi yang mandiri dan serbaguna yang dirancang untuk menciptakan komunitas pembelajaran kreatif yang tidak membatasi yang memenuhi kebutuhan mahasiswa Penelitian ini bertujuan untuk untuk melihat dampak dan persepsi penerapan Merdeka Belajar Kampus Merdeka (MBKM) kepada seluruh mahasiswa di perguruan tinggi swasta dengan tujuan untuk melihat sejauh mana pemahaman dan persepsi mahasiswa dan dampak dari penerapan program Merdeka Belaj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
22

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 7 publications
(7 reference statements)
1
19
0
22
Order By: Relevance
“…In line with the results of this study, the policy of implementing MBKM in several other universities was reported to have given a positive response for students after getting experience that increased their competence, especially those directly related to the field of work they would face after graduation (Meke et al, 2022;Sari et al, 2021;Waskitaningsih et al, 2022;Yuherman et al, 2021). Students assess the implications of implementing MBKM to improve 21st century skills (Waskitaningsih et al, 2022), to solve complex problems, broaden perspectives, prepare for work after graduation, increase soft skills and prepare for the post-campus period (Septiani et al, 2022) (Pohan & Kisman, 2022).…”
Section: Student Interest In Mbkm Activitiessupporting
confidence: 84%
See 1 more Smart Citation
“…In line with the results of this study, the policy of implementing MBKM in several other universities was reported to have given a positive response for students after getting experience that increased their competence, especially those directly related to the field of work they would face after graduation (Meke et al, 2022;Sari et al, 2021;Waskitaningsih et al, 2022;Yuherman et al, 2021). Students assess the implications of implementing MBKM to improve 21st century skills (Waskitaningsih et al, 2022), to solve complex problems, broaden perspectives, prepare for work after graduation, increase soft skills and prepare for the post-campus period (Septiani et al, 2022) (Pohan & Kisman, 2022).…”
Section: Student Interest In Mbkm Activitiessupporting
confidence: 84%
“…Students assess the implications of implementing MBKM to improve 21st century skills (Waskitaningsih et al, 2022), to solve complex problems, broaden perspectives, prepare for work after graduation, increase soft skills and prepare for the post-campus period (Septiani et al, 2022) (Pohan & Kisman, 2022). In addition, the implications of implementing MBKM through student exchange activities, namely increasing competence and adding experience outside of the study program background so that they are able to develop other competencies to help them in the world of work such as communication skills, be more diligent because they are motivated from other college friends achievement and have many acquaintances (Anggraini & Siska, 2021;Masitoh et al, 2021;Meke et al, 2022;Pohan & Kisman, 2022;Septiani et al, 2022).…”
Section: Student Interest In Mbkm Activitiesmentioning
confidence: 99%
“…al., 2021). This shows the hope and confidence that students build in the success of the MBKM program in helping students get good jobs after graduating from college (Meke, Astro & Daud, 2022). 9 shows that positive responses were also given by the respondents from the Information Systems Study Program to the questionnaire items.…”
Section: Figure 8 Student Survey On Respondents' Positive Responses T...mentioning
confidence: 78%
“…Dalam implementasinya, tentu dirasa penting untuk melihat sejauh mana kegiatan implementasi tersebut berjalan. Dengan kata lain, perlu dilakukan survei untuk melihat sejauh mana Implementasi MBKM dapat berjalan terlebih dimasa pandemic covid 19 (Meke, Astro & Daud, 2021;Laga, dkk., 2021). Hail ini tentu membantu baik pihak perguruan tinggi maupun program studi untuk bisa mengetahui minat, kendala dan juga rencana tindak lanjut yang dapat dijadikan bahan evaluasi dan juga konsep dalam penentuan strategi berikutnya (Nona, dkk., 2021).…”
Section: Pendahuluanunclassified